Design and test validation of a novel low-cost quartz window for reducing heat losses in concentrating solar power applications - Sullivan, Shaun D.; Kesseli, James B. (AIP conference proceedings, 2019)
Concentrating Solar Power (CSP) continues to see increased deployment with nearly 5 GW of CSP installed worldwide. CSP is particularly attractive as a renewable energy source given that the storage and recovery of absorbed heat may be accomplished using sensible, latent, or thermochemical systems; this enables cost-effective deferral and on-demand dispatch of electricity generated from CSP, addressing mismatches between power demand and solar availability. Power tower and dish-based CSP configurations, in which reflected solar energy is focused onto a single central target, can generate very high temperatures; this enables the use of supercritical steam cycles, air Brayton cycles, or supercritical carbon dioxide (sCO2) power cycles that produce electricity at higher efficiencies than can be achieved with photovoltaic (PV) or linear-focus trough-based CSP systems. Critical to the performance and economics of all CSP systems is their ability to retain as much of the captured solar energy as possible. Heat losses to the environment directly penalize the efficiency of the system, requiring additional collector area to achieve the target power. The receiver, through which solar energy is absorbed and conveyed as heat into a working fluid, is necessarily the highest-temperature component in the system; as a result it has the greatest potential to lose heat via radiation to the environment. Furthermore, convection losses from the high temperature absorber to the ambient environment may also be high. Historically quartz windows have been employed in conjunction with cavity-type receivers, which are suitable for dish- mounted and small-scale power tower applications. Quartz is naturally transparent to wavelengths of visible light but is opaque to a large fraction of infrared wavelengths. Consequently, concentrated solar energy passes through a quartz surface unimpeded, but a significant fraction of the infrared radiation that might otherwise be lost from the hot absorber surface to the environment is absorbed by the window; this provides a radiation shield and reduces heat losses. The window may also impede the formation of convection cells, further reducing heat losses. These benefits must be weighed against the penalties imposed by the inclusion of a quartz window. For example, for every window surface that incoming light passes through at greater than its critical angle, there is a 4% reflection loss; this corresponds to a total energy loss of 7.8% in the case of a standard planar window, accounting for reflection losses at both front and back faces. Therefore the window is only practical if reduces heat losses by at least this amount. Furthermore, the cost of incorporating a quartz windows can be prohibitive, particularly in larger sizes (corresponding to larger power ratings and/or non-cavity receivers), more complex forms designed to reduce reflection losses, and for systems in which the window must react elevated internal pressures. To address these shortcomings Brayton Energy has developed, analyzed, and tested a novel quartz tube window system. This configuration employs commodity-priced thin-walled quartz tubes with L/D ratios of 3 or more. These tubes are arrayed in a close-packed configuration and mounted over the receiver aperture. Incoming concentrated sunlight only encounters thin tube wall surfaces at an angle exceeding the critical angle; consequently, the fraction of the aperture that is subject to the 4% reflection loss is very small. All other surface encounters occur along the lateral surface of the tube walls at an incident angle below the critical angle, resulting in reflections that redirect the light deeper into the cavity as opposed to back out to environment. Depending upon the specific receiver and absorber element configuration, a quartz-tube window design may be also implemented such that it impedes convection cells; this can further reduce heat losses to the environment and improve overall system efficiency. The design, analysis, fabrication, installation, and performance testing of quartz tube windows for two different receiver configurations will be reported here. These studies indicate that for the receiver applications studied, inclusion of a quartz tube window has the potential to dramatically reduce the thermal losses at the design point. Validation testing was performed to directly measure heat loss from systems at operating temperatures appropriate for a sCO2 power block both with and without the quartz tube window in place. Inclusion of a quartz tube window to the cavity receiver decreased its design point heat loss by up to 33%, depending on the receiver tilt angle. The addition of a quartz tube window to an open receiver module decreased its combined radiative and convective heat losses by more than 50%.